Predictors and outcomes of nurses’ use of smartphones for work purposes - BAUTISTA, John Robert (Institutional Knowledge at Singapore Management University, 2018)
Recent studies have indicated that nurses use their smartphones for work purposes to enhance productivity. However, few theory-driven quantitative studies have examined factors associated with such use. This study aims to address this research gap by developing and testing a model based on the theory of planned behavior, organizational support theory, and IT consumerization theory. Hypothesis testing used structural equation modeling of survey data from 517 staff nurses employed in 19 tertiary-level general hospitals in the Philippines. Results showed that injunctive norm, descriptive norm, and perceived behavioral control were positively associated with intention to use smartphones for work purposes. Moreover, intention was positively associated with nurses' use of smartphones for work purposes. Interestingly, nurses' use of smartphones for work purposes was positively associated with perceived work productivity and perceived quality of care. An alternative model examines how perceived organizational support indirectly affects nurses’ use of smartphones for work purposes. The discussion considers theoretical and practical implications.